Building simulation to determine self-shaded form for high-rise buildings - Chia, Sok Ling (Penerbit UTM, 2008)
The chapter discusses the met hodology used in investigating th e optimum geometric shape high- rise built form and effectiveness of self-shaded high-rise built form for hot and humid climate. The discussion is divided into two phases. Phase one consists of case study of the generic high- rise building shape in Kuala Lumpur and adapta tion of self-shading stra tegy in high-rise built form. Three base models are developed based on the above said studie s. Second phase reviews the research methodologies used by previous researchers. The justification of the selected methodology of this study is elaborated. Finally, the experimental procedures, limitations and overall sequence of the experimental method are di scussed. There is lack of research on the solar radiation prevention especially in equatorial tropics. The devel opment of self-shaded high-rise built form to achieve maximum reduction of solar isolation on its external exposed surface is crucial. Impact of solar radiation on the external surfaces of high-rise is important to determining the optimum geometric shape and adaptation of self shading stra tegy into high-rise building design. The shading strategy is more efficient if able to apply at the early stag e of high rise building design. Since it is in the early stages, the most significant deci sions are easily and appropriately made regarding sizing, form, pl acement and orientation of the building volume.